Cost-minimisation analysis of acute myocardial infarction rule-out in low-risk patients: primary care emergency setting versus hospital setting. (14th October 2021) - Johannessen, T R; Halvorsen, S; Atar, D; Wisloff, T; Munkhaugen, J; Nore, A K; Vallersnes, O M
Abstract: Background: Hospital management of low-risk chest pain contributes to extensive use of healthcare resources and emergency department crowding. High efficacy rule-out, with subsequent reduction in costs and length of stay, has been demonstrated for the ESC 0/1-hour algorithm using high-sensitivity cardiac troponins (hs-cTn) in hospital cohorts. Purpose: To estimate potential differences in healthcare costs by assessing patients with low risk for acute coronary syndromes (ACS) in a primary care emergency setting using the ESC 0/1-hour algorithm compared to routine management in a hospital setting. Methods: This cost-minimisation analysis compared direct costs of applying the 0/1-hour algorithm in a low-risk primary care cohort to a low-risk chest pain cohort at a large general hospital in Norway. Data from the prospective OUT-ACS study (One-hoUr Troponin in a low-prevalence population of Acute Coronary Syndrome, [1] inclusion period 2016–2018) were used to calculate costs per patient at a primary care emergency clinic. For the hospital setting estimates, anonymous data were extracted for all low-risk chest pain patients treated at a large general hospital in 2018. Cost items include complete hospital costs per different diagnosis-related groups as defined in national assessments, as well as resource items required to use the algorithm in primary care, including personnel time and test- and treatment costs. Primary outcome was the difference in healthcare costs when assessing the low-risk cohort in a primary care setting compared to a hospital setting. The secondary outcome was the difference in length of stay. Results: The costs of assessing the low-risk cohort at the primary care emergency clinic and the general hospital were estimated at €178 and €1480, respectively (Table 1). Thus, the estimated reduction in health care costs among patients assessable by the 0/1-hour algorithm outside of hospital was €1302 per patient, with a mean decrease in length of stay of 18.9 hours. Additional diagnostic procedures (e.g. stress ECG and echocardiogram) were performed in 31.9% (n=181/567) of the low-risk hospital cohort, which was part of the cost-driving estimate. Conclusion: Assessment of patients considered as low-risk for ACS with the ESC 0/1-hour algorithm in a primary care emergency setting seems to decrease healthcare costs significantly, in addition to a reduction in both length of stay and potentially unnecessary hospitalisations. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Norwegian Research Fund for General PracticeThe Norwegian Committee on Research in General Practice